2011
DOI: 10.1364/oe.19.023809
|View full text |Cite
|
Sign up to set email alerts
|

Giant tunable optical dispersion using chromo-modal excitation of a multimode waveguide

Abstract: The ability to control chromatic dispersion is paramount in applications where the optical pulsewidth is critical, such as chirped pulse amplification and fiber optic communications. Typically, devices used to generate large amounts (>100 ps/nm) of chromatic dispersion are based on diffraction gratings, chirped fiber Bragg gratings, or dispersion compensating fiber. Unfortunately, these dispersive elements suffer from one or more of the following restrictions: (i) limited operational bandwidth, (ii) limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Despite extensive theoretical and simulation studies on the AST approach including this work, quite little experimental study on this topic has been reported so far, mainly due to the lack of good optical filter offering an engineered group delay or dispersion profile. Potential good candidates to achieve the particularly designed AST filter include customized fibre Bragg gratings [14,22,23], chromo-modal dispersion mechanism [24] with the aid of mode-selective excitation [25], and photonic crystal fibre (PCF) with precisely controlled chromatic dispersion profile [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive theoretical and simulation studies on the AST approach including this work, quite little experimental study on this topic has been reported so far, mainly due to the lack of good optical filter offering an engineered group delay or dispersion profile. Potential good candidates to achieve the particularly designed AST filter include customized fibre Bragg gratings [14,22,23], chromo-modal dispersion mechanism [24] with the aid of mode-selective excitation [25], and photonic crystal fibre (PCF) with precisely controlled chromatic dispersion profile [26].…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment the source spectral width is measured with an optical spectrum analyzer and converted to coherence time t c . To excite a large number of modes we overfill the acceptance angle of the MMF by tightly focusing the initially fully spatially coherent light on the input face of the MMF [25]. The position of the focus is not centered on the core of the MMF in order to excite all possible skew rays in the fiber.…”
Section: Methodsmentioning
confidence: 99%
“…7b) [32], [33], the ChromoModal Dispersion (CMD) device (Fig. 7c) [34], and the reconfigurable optical add-drop multiplexers (ROADMs) [35], [36]. The CFBG is a distributed Bragg reflector (periodic variation in the refractive index) written in a short segment of an optical fiber that reflects particular wavelengths of light and transmits all others (Fig.…”
Section: Optical Implementations and Reconfigurabilitymentioning
confidence: 99%
“…The CMD is a type of dispersive device that converts the large modal (spatial) dispersion inherent in multi-mode fibers or waveguide to chromatic (frequency dependent) dispersion ( Fig. 7c) [34]. It does so by combining the waveguide with a diffraction grating.…”
Section: Optical Implementations and Reconfigurabilitymentioning
confidence: 99%